A Comparative Study of AG*-groupoidsy - Ahmad, I.; Naz, R.; Rashad, M.; Khan, A. (The Nucleus, 2016)
A magma satisfying the identityis called an LA-semigroup or AG-groupoid. We investigate the concept of AG*-groupoid, as a subclass of AG-groupoids and establish some relations of AG*-groupoids with other known subclasses of AG-groupoid, like: Stein, Stein*, Jordan and Schroder AG-groupoids. Furthermore, we use the latest computational techniques of Mace-4 and Prover-9 to provide various examples and counterexamples for our relevant investigation.